(untitled) (Revista Contexto & Educação, 2022)
Youth protagonism gains a theoretical foundation in Brazil with the work of pedagogue Antonio Carlos Gomes da Costa in the 1990s, based on the experience of working with young people in non-governmental organizations. This role is inspired by what became known as the Jacques Delors Report, which sets out the four pillars of an “Education for the 21st century”, namely, learn to be, learn to do, learn to learn and learn to live together. With this role, the young person would form his autonomy from an experience more focused on his own competences and abilities. Based on a documentary analysis inspired by Foucault’s work, we seek to analyze the discourse of youth protagonism in connection with the reinterpretation that the philosopher develops of the notion of human capital. We argue in this text that youth protagonism, in addition to being linked to a strategy of investing in the “potential of youth” for the social development of a population, is also a biopolitical strategy for the formation of an entrepreneurial culture with a view to economic and social development from the country.